PENGEMBANGAN APLIKASI BIMBINGAN KONSELING PADA SMK NEGERI 1 MUARA TEWEH MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Jadiaman Parhusip; Ade Saputra; Caca Handika; Indes Permatahati Parhusip (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
The development of counseling guidance applications at SMK Negeri I Muara Teweh aims to help related parties to use information technology and computers in managing data related to student character building, namely the achievements achieved and the violations committed by each student, if any. The difficulty experienced by the school's Guidance and Counseling party is recording daily, weekly, monthly and even yearly data for all students, which is not small in number. So far, data processing is still manual and feels very inconvenient because of the various attributes of the types of violations that must be assessed with different weights, so that to be able to make a decision requires tiring and time-consuming calculations. Using a web-based application is expected to be able to reach more users, namely counseling guidance teachers as admins, students, and parents of students. Another benefit is to achieve a fair and objective assessment so that decisions made by schools are based on data that is processed using a computer. The process of making this application uses the PHP and HTML programming languages while the database uses MySQL. The system development method uses the Rapid Application Development (RAD) method. Unified Modeling Language (UML) diagram design tool consisting of use case diagrams, class diagrams, and activity diagrams